The Role of Human Resources in Comprehensive Regional Sustainable Development: The Case of Azerbaijan - Alakbarov, Urkhan; Habibova, Ziyafat; Rahimli, Rajab (International Journal of Economics and Financial Issues, 2020)
The main objective of sustainable and comprehensive economic development is the successful implementation and integration of human resources into national programs and development policies. To attain such all-inclusive and maintainable levels of development, the fundamental elements of economic growth, inclusive societies and the environmental protection should be harmonized with each other. With the understanding that a strong correlation exists between human resources and sustainable economic development, states and governments should adopt policies that effectively address these interconnected elements in order to reach the goal of prosperity of individuals under the slogan “inclusive societies”. In accordance with this framework, the Sustainable Development Goals (SDGs), which are reflected in the Sustainable Development 2030 Agenda, define the priorities for regional sustainable comprehensive development and relate the strategies necessary for implementation of human capital plans. Countries in the Caspian Sea basin, such as the Republic of Azerbaijan, are currently in the process of further integrating their human resource capacities into the general development of the country. This paper analyzes further positive economic results along with effective human governance through the use of new principles and contemporary technologies. Keywords: Human Resources, National Programs, Development Policies, Azerbaijan, Caspian Sea. JEL Classifications: O15, P48, Q01 DOI: https://doi.org/10.32479/ijefi.9303